A brief history of citizenship - Heater, Derek Benjamin (Edinburgh University Press, 2004)
This work is an introductory survey of the history of the principles and practice of citizenship, based on the premise that the conditions and debates about citizenship cannot be fully understood without a knowledge of the historical background.